Neonatal androgenization-induced early endocrine–metabolic and ovary misprogramming in the female rat - Ongaro Gambino, Luisina (2015)
Aim: Androgen excess predisposes the organism to develop metabolic–endocrine and reproductive dysfunctions, among them the development of a phenotype resembling that of human Polycystic Ovary Syndrome (PCOS). Methods: We analyzed the impact of a single neonatal (5 day-old) testosterone propionate (TP; s.c. 1.25 mg/female pup) dose on: a) several metabolic–endocrine activities and b) ovarian steroidogenic and granulosa cell (GC) functions and also follicular population in juvenile and adult TP and control (CT) rats. Key findings: Compared to CT rats, TP animals were characterized by: a) accelerated growth, hyperadiposity and hyperleptinemia, b) very early (pre-weaning age) vaginal opening, c) hyperinsulinemia in adult life, d) dysfunctional ovarian steroidogenesis, e) conserved GC functionality in both juveniles (in vitro) and adults (in vivo), and f) estrous cycles arrested at estrus. Finally, histological studies of the ovaries indicated that in TP (vs. CT) rats: i) primary and antral follicle frequencies were 3- and 15-fold higher and lower, respectively, in juveniles and ii) secondary and atretic follicle frequencies were 3- and 5-fold lower and higher, respectively, in adults. Large cystic images without corpus luteum were observed in the ovaries from adult TP rats only. Significance: Our results strongly suggest that transient neonatal hyperandrogenemia induced early misprogramming of metabolic–endocrine and ovarian (steroidogenesis/folliculogenesis) functions. Conversely, TP rats preserved their ovary GC endocrine function. Our results further support the high risk of developing ovarian hyperstimulation syndrome for infertile women with transient/chronic hyperandrogenemia (PCOS) subjected to assisted reproductive technologies.